ABSTRACTS - Revista Venezolana de Análisis de Coyuntura, . (Revista Venezolana de Análisis de Coyuntura, 2016)
Organic Law on the Financial Administration of the Public Sector. Contents, Importance and Limitations. Economic Aspects of the Reform of Venezuela’s Organic Tax Code in 2001. Establishing the Basis for the Added Value Tax and Elements for Calculating the Gap Between Potential and Effective Income. The Theory of Financial Preadjustment: Some Empirical Indicators. Public Social Expenditure in Venezuela: A History of Winners or Losers?. Financing Higher Education in Latin America (With Special Emphasis on = Public Financing). Productivity in the Private Sector, 1983-1999. The Gas Era?. Logistics in Tourist Activity. The Participation Rate in the Venezuelan Labor Market, According to Instruction Level, Sex and Age, 1977-1997. Maximum Credible Estimates in Biplot Approximations. Pilot Test and Validation of the Synthetic Poverty Index. Analysis of the theoretical explanations of the process of price formation. Their applicability for the case of the price of chicken.